2020
DOI: 10.1111/1750-3841.15358
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical profiles, antioxidant, and antiproliferative activities of red‐fleshed apple as affected by in vitro digestion

Abstract: The aim of this study was to characterize the phenolic profiles in the extracts and digesta (after in vitro digestion) of different red‐fleshed apple fruit parts and to assess the effects of digestion on the in vitro antioxidant capacity and antiproliferative activity. The main polyphenols were identified by UPLC‐MS/MS and HPLC. Our results indicate that the digesta had less total phenolics, flavonoids, and anthocyanins, but more free phenolic acids, than the extracts. An analysis of the in vitro antioxidant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…Since RAAE is a mixture of various components, it is unclear which bioactive ingredient (s) in anthocyanins played the role in alleviating the adverse effects induced by busulfan. In this regard, we identified cyanidin 3-O-galactoside as the most abundant anthocyanin, consisting of what was observed in other red-fleshed apples by previous studies (24,43). It will be interesting to examine whether cyanidin 3-O-galactoside might be the active component that is able to reduce the adverse effect caused by busulfan in mice.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Since RAAE is a mixture of various components, it is unclear which bioactive ingredient (s) in anthocyanins played the role in alleviating the adverse effects induced by busulfan. In this regard, we identified cyanidin 3-O-galactoside as the most abundant anthocyanin, consisting of what was observed in other red-fleshed apples by previous studies (24,43). It will be interesting to examine whether cyanidin 3-O-galactoside might be the active component that is able to reduce the adverse effect caused by busulfan in mice.…”
Section: Discussionsupporting
confidence: 60%
“…The analysis showed the anthocyanin content in the peel and flesh of red-fleshed "XJ4" to be over 400 mg/kg FW (Figure 1), which is much higher than the anthocyanin content of typical commercial white-fleshed cultivar "Fuji" by about 8 mg/kg FW (24). It has been suggested that the damage induced by busulfan to the spermatogenesis is mainly due to oxidative stress and lipid peroxidation (5,6,42).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The cytotoxicity assay toward MCF‐7 and MDA‐MB‐231 human breast cancer cells was performed according to a previously described method by Li et al. (2020).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, Red-fleshed apple is a natural antioxidant with significant antioxidative activities and liver protective effects. Study found that among the four species studied, “Roberts Crab” had the highest content of total phenols, flavonoids and anthocyanins, and the strongest scavenging ability on DPPH, ABTS, and FRAP ( 5 ).…”
Section: Introductionmentioning
confidence: 99%